2021
DOI: 10.2139/ssrn.3924099
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Barriers and the Socioeconomic Gap in Child Care Enrollment

Abstract: Children with lower socioeconomic status (SES) tend to benefit more from early child care, but are substantially less likely to be enrolled. We study whether reducing behavioral barriers in the application process increases enrollment in child care for lower-SES children. In our RCT in Germany with highly subsidized child care (n > 600), treated families receive application information and personal assistance for applications. For lower-SES families, the treatment increases child care application rates by 21 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…(2018) instead comprises those children in parental care, who are, on average, more socioeconomically disadvantaged (Hermes et al . 2021). Moreover, Cornelissen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) instead comprises those children in parental care, who are, on average, more socioeconomically disadvantaged (Hermes et al . 2021). Moreover, Cornelissen et al .…”
Section: Resultsmentioning
confidence: 99%
“…of the population, compared to those who remain in parental care. The untreated sample ofCornelissen et al (2018) instead comprises those children in parental care, who are, on average, more socioeconomically disadvantaged(Hermes et al 2021). Moreover, Cornelissen et al (2018 compare the impacts of parental care versus non-parental care on cognitive and motor skills, and health, rather than on non-cognitive skills, and for a country (Germany) that appears to demonstrate positive consequences of CBC.…”
mentioning
confidence: 99%
“…Even though some studies in Germany have found strong relations between family risk and behavior regulation in children (e.g., Deffaa et al, 2020;Pitzer et al, 2011), other studies point out effects of more distal contextual aspects that might be relevant for children's development in Germany. Some studies revealed that children in Germany with high family risk profit highly from childcare enrollment, which is subsidized in the German social-welfare system, so that it is affordable for everybody (Hermes et al, 2021;Hübenthal and Ifland, 2011). As we contacted our participants in Germany through schools and social workers, participating families were in contact with social workers already and thus they might have been integrated into a social support system that might have buffered the effect of a high family risk.…”
Section: Family Risk Maternal Restrictive Control and Behavior Regula...mentioning
confidence: 99%
“…A significant practical problem with all early childhood education programs is that, while benefits appear to be greatest for the most disadvantaged children (Cornelissen et al, 2018;Gray-Lobe et al, 2021;Havnes and Mogstad, 2015), take up is much greater for the children of the advantaged (e.g., Hermes et al, 2021). Outreach is an important issue that needs to be actively addressed if these programs are to be successfully implemented on a wide scale.…”
Section: Introductionmentioning
confidence: 99%